Hidden in plain sight: SAS doctors fight for fair pay. (8th March 2023) - Kochhar, Amit
Abstract : Specialist, associate specialist, and specialty doctors feel like an afterthought, but we can value them by recognising their work and paying them fairly, writes Amit Kochhar